Exploring factors contributing to limited adoption of artificial intelligence in recruitment within FMCG Industry in Bangladesh - Afza, Omar Md. (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.